Comparative mesocosm study of biostimulation efficiency in two different oil-amended sub-antarctic soils - Delille, Daniel; Coulon, Frederic (Springer, 2008)
Biological treatment has become increasingly popular as a remediation method for soils and groundwater contaminated with petroleum hydrocarbon, chlorinated solvents, and pesticides. Bioremediation has been considered for application in cold regions such as Arctic and sub-Arctic climates and Antarctica. Studies to date suggest that indigenous microbes suitable for bioremediation exist in soils in these regions. This paper reports on two case studies at the sub-Antarctic Kerguelen Island, in which indigenous bacteria were found that were capable of mineralizing petroleum hydrocarbons in soil contaminated with crude oil and diesel fuel. All results demonstrate a serious influence of the soil properties on the biostimulation efficiency. Both temperature elevation and fertilizer addition have a more significant impact on the microbial assemblages in the mineral soil than in the organic one. Analysis of the hydrocarbons remaining at the end of the experiments confirmed the bacterial observations. Optimum temperature seems to be around 10°C in organic soil while it was higher in mineral soil. The benefit of adding nutrient was much stronger in mineral than in the organic soil. Overall, this study suggests on the basis of microbiological and physicochemical parameters, that biostimulation treatments were driven by soil properties and that ex-situ bioremediation for treatment of cold contaminated soils will allow greater control over soil temperature, a limiting factor in cold climates.
Keywords: sub-antarctic; oil; biostimulation; cold environments; degradation; crude oil; diesel fuel